Teacher Quality Development Management In Improving The Quality of Graduates at Madrasah Aliyah Negeri 3 Langkat - Suparliadi, Suparliadi; Wijaya, Candra; Daulay, Nurussakinah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Study This aim is to: 1) know planning development internal teacher quality enhancement quality graduates at Madrasah Aliyah Negeri 3 Langkat; 2) know implementation development internal teacher quality enhancement quality graduates at Madrasah Aliyah Negeri 3 Langkat; and 3) know supervision development internal teacher quality enhancement quality graduates at Madrasah Aliyah Negeri 3 Langkat. Research methods in qualitative research Where data collection techniques use interviews, observations, and study documents, To strengthen the validity of the result data findings and authenticity research, researchers refer to using the standard validity of the data suggested by Lincoln & Guba, consisting of credibility, transferability, dependability, and confirmability. Research result This in the form of: 1) Planning development internal teacher quality enhancement quality graduates at Madrasah Aliyah Negeri 3 Langkat, carried out with the choice of a development program competence appropriate teacher professionalism with needs; yes, replace existing programs accomplished or add another program. the program, including training, workshops, MGMP, KKG, and writing scientific work. 2) Implementation of improvement programs for quality teacher professionalism at MAN 3 Langkat is done after the planning and organizing process has been completed. The head of MAN 3 Langkat, along with the deputy head of the madrasa and the teachers, have realized the work program that has been implemented previously with full commitment and responsibility. This matter This can be seen from the training carried out, including: the 2013 curriculum, which was implemented each semester; MGMP activities carried out by each eye teacher; motivation for teachers who will continue study; 3) Supervision to enhance quality teacher professionalism at MAN 3 Langkat is carried out by the head of the madrasah. Various supervision is done in accordance with the task principal and function of each. Monitoring direct teacher performance, neither in class nor with CCTV equipment, and evaluating results, especially teacher performance achievement, of the work program in enhancement quality teacher professionalism.